2022
DOI: 10.3390/nu14163400
|View full text |Cite
|
Sign up to set email alerts
|

The Menu Served in Canadian Penitentiaries: A Nutritional Analysis

Abstract: The food served in Canadian penitentiaries was scrutinized following food service reform where Correctional Service Canada (CSC) created a standardized menu to feed incarcerated male individuals. Food in prison is a complex issue because penitentiaries are responsible for providing adequate nutrition to the prison population, who are vulnerable to poor health outcomes but are often seen as undeserving. This study aimed to analyse the national menu served in Canadian penitentiaries, in order to compare them wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A study on the nutrient balance of prison menus in Poland [ 24 ] found that daily caloric intake was 2708 kcal, indicating an intake level similar to that of the KSA. The issue of excessive calorie intake is more pronounced in countries such as Canada (+22% and +45% of the DRI for men and women, respectively) [ 25 ]. In less developed economies such as Ghana [ 26 ], the caloric intake is nearly 9% lower than the DRI for men and 9% higher for women.…”
Section: Discussionmentioning
confidence: 99%
“…A study on the nutrient balance of prison menus in Poland [ 24 ] found that daily caloric intake was 2708 kcal, indicating an intake level similar to that of the KSA. The issue of excessive calorie intake is more pronounced in countries such as Canada (+22% and +45% of the DRI for men and women, respectively) [ 25 ]. In less developed economies such as Ghana [ 26 ], the caloric intake is nearly 9% lower than the DRI for men and 9% higher for women.…”
Section: Discussionmentioning
confidence: 99%
“…This leads us to consider whether the effects seen across the supplementation studies were attributed to a mechanism involving the vitamin and minerals component. Vitamin D is notorious for being deficient in populations globally, and in the context of a prison, this deficiency is more likely due to limited access to sunlight (25,54,55) . Among the included studies, Gesch et al (48) found that vitamin D was deficient based on the baseline dietary assessment, with prisoners, on average, having an intake of 3•5 μg, while the current dietary recommendations suggest 10 μg per d (56) .…”
Section: Dietary Supplementsmentioning
confidence: 99%